The Effect of Exports, Imports And Exchange Rates On The National Foreign Exchange Reserves 2000-2019 - Jacobus Cliff Diky Rijoly; Desry Jonelda Louhenapessy; Jodi Aleksander Panggabean (MediaTrend, 2023)
This study intends to assess the shock from national foreign exchange's primary variables, such as exports, imports, and exchange rates, for the period 2000-2019. The data utilized in this study came from the Indonesian Statistics Bureau (BPS), the Bank of Indonesia (BI), and the World Bank 2021. For this analysis, we utilize an autoregressive framework to capture the shock and explain its long-term influence on a country’s foreign exchange reserves. The results of the VECM study indicate that exports have a large, long- and short-term positive influence on foreign exchange reserves, whereas imports have no effect on foreign exchange reserves and the exchange rate has a considerable effect on Indonesia's foreign currency reserves. On national foreign exchange reserves, exports have a positive impact, imports a negative impact, and the exchange rate has a substantial impact.